ANALISIS KEMAMPUAN DRIBBLING SEPAK BOLA (SURVEI PADA SEKOLAH SEPAK BOLA LABONSA) - Prastyo, Aldi; Jariono, Gatot; Fatoni, Muhad (Universitas Hamzanwadi, 2025)
The purpose of this study was to determine the level of dribbling ability of Labonsa Wonoharjo soccer school students. The method used in this research is quantitative method, survey method and data collection in this study using slalom dribble test instrument. The population of this study was 30 people from Labonsa soccer school and the sampling technique was total sampling. The results of this study based on the results of descriptive analysis of the frequency of dribbling ability research data at SSB Labonsa, the category that has the greatest frequency and percentage of samples is the high category with 15 students (50%), and the smallest is the very high category with 0 students (0.01%), for the medium category there are 7 students (23.33%), for the low category 4 students (13.33%), and for the very low category 4 students (23.33%). The mean value of 19.56 lies in the interval 18.90-20.24. This research data is divided into five categories with intervals, namely for very high categories ( < 17.55), high (17.56-18.89), medium (18.90-20.24), low (20.25-21.58), very low ( > 21.58). So the conclusion is that the level of dribbling ability of SSB Labonsa students is in the moderate category.